Trichterbecherkultur in Nordmitteleuropa: Bevölkerungsdichte, Kommunikationsstrukturen und Traditionsräume - Rassmann, Knut (e-Forschungsberichte des DAI, 2023)
During the 4th millennium BC in northern Central Europe, social changes took place which led to the building of monumental grave architecture. The detailed analysis of the architecture of megalithic graves is based on the processing of specific single architectural features. The monument biographies include their erection, modifications in construction, changes in function, and, more generally, the alternation process at funeral and burial rites. In combination with the analysis of archaeological objects, architecture has been investigated on various scales. The goals are to model demographic processes, to reconstruct communication structures and to reveal traditions in architecture and the use of the social and political space. Key questions of our research concern how far megalithic architecture indicates cultural and social traditions and what exactly the nature of those social structures within Neolithic societies were.